Ordinary care in extraordinary times. (11th December 2022) - Patel, S.; Gannon, A.; Cryan, M.; McDonnell, N.; Rafiq, S.; Adamis, D.; Dolan, C.; McCarthy, G.
Abstract : The Coronavirus Disease 2019 (COVID-19) has accounted for more than 25 000 cases in Ireland with approximately 28% of the clusters in nursing homes as of June 2020. The older population is the most vulnerable to serious complications from this illness and over 90% of deaths due to COVID-19 to date have been in patients over the age of 65. Continuing to provide routine care within nursing homes in these challenging times is an essential part of ensuring that presentations to hospitals for non-essential reasons are minimized. In this article, we describe a project being undertaken by a rural Psychiatry of Old Age Service in the northwest of Ireland. We aim to provide ordinary care in extraordinary times by using mobile tablets within the nursing homes and long-stay facilities in our region for remote video consultations during the COVID-19 crisis.